ESTRATÉGIAS DE ECOINOVAÇÃO NA IMPLANTAÇÃO DA ISO 14001: ESTUDO DE CASO EM UMA INDÚSTRIA DE PAPEL E SUA CADEIA DE SUPRIMENTOS - CROTTI, KATIANE (2016)
The research is established on evolutionary theory, which deals with the role of innovation to economic and organizational development. The theory broaches that capitalist competition requires differentiation, so that organizations can develop and can be competitive on the market. Therefore, innovation must be a constant search by organizations, because they need to keep up with the demands of their customers. The survey broke the assumption of the need for companies to innovate in the environmental area, to respond to the market, improve the corporate image, as well as meet the environmental legislation.For that, we did a case study at Ibema Cia Brasileira de Papel because they were in the process of innovation to obtain the certification ISO 14001:2004. Thus, the dissertation aimed to analyze the strategies of General eco-innovation in the implementation of the ISO 14001 certification, in an industry of the pulp and paper sector in the South-Central region of Paraná and its supply chain. To this end, the following specific objectives have been defined: verify certification deployment actions in the internal environment and supply chain; back up and analyze the strategies of eco-innovation that emerged of certification; and meet the perspectives of organizational results after achiving the certification. The methodological approach chosen was mixed, being a qualitative and quantitative study. The data collection instruments were document analysis, observation and interviews with responsible for Environment and high management of the company. Also been applied questionnaires, answered by 342 employees and 16 industry´s suppliers. For qualitative data analysis, content analysis, while quantitative data analyses were conducted descriptive statistics such as mean, standard deviation and coefficient of variation. And also the data of the questionnaire was submitted to factor analysis, which generated 9 factors and cluster analysis, which was applied to the data suppliers. As result of the research, it was found that the industry had to adapt and innovate to win certification, developing strategies of eco-innovation that facilitated this process. The search for the certification influenced the company´s environment and its supply chain. So, it was identified that the industry is achiving the desired results, because the strategies of eco-innovation brought reduced raw material consumption and preservation of the environment. In addition, the certification provided the environmental awareness of employees, suppliers and of senior management, which proved to be quite committed to environmental effectiveness. However, it turned out, from the research, an opportunity for Ibema to improve the way to transmit your concern with the preservation of the environment, as well as the way to divulge his environmental policy to suppliers.